2019
DOI: 10.1016/j.ekir.2018.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Evaluation of Patiromer for the Treatment of Hyperkalemia in Hemodialysis Patients

Abstract: IntroductionPatiromer is a potassium (K+) binding polymer indicated for treating hyperkalemia. Among patients receiving chronic hemodialysis (HD), this study aimed to identify patient characteristics associated with patiromer initiation, describe patiromer utilization, and analyze serum K+ pre- and post-patiromer initiation.MethodsIn a retrospective cohort study, using electronic health record data from a large dialysis provider in the United States (study period: December 21, 2015, to December 20, 2016), HD p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
46
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 17 publications
1
46
0
1
Order By: Relevance
“…This compares to 0% of patients with a K + concentration <5.1 mmol/L and 19% with <5.5 mmol/L before initiating patiromer (Figure 3). A similar percentage of patients achieving normokalemia (K + <5.1 mmol/L) was reported in two prospective, randomized trials (AMETHYST-DN [77%-95%] and OPAL-HK [76%]) [23,24].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This compares to 0% of patients with a K + concentration <5.1 mmol/L and 19% with <5.5 mmol/L before initiating patiromer (Figure 3). A similar percentage of patients achieving normokalemia (K + <5.1 mmol/L) was reported in two prospective, randomized trials (AMETHYST-DN [77%-95%] and OPAL-HK [76%]) [23,24].…”
Section: Discussionsupporting
confidence: 72%
“…This is the first study to provide an early report about patiromer utilization among US Veterans with HK. Recently, a real-world analysis of patiromer for the treatment of hyperkalemia in chronic hemodialysis patients was published [23]. However, to our knowledge, no other published studies have evaluated HK management with patiromer in a real-world setting of primarily CKD patients.…”
Section: Discussionmentioning
confidence: 99%
“…105 A recent retrospective analysis of 527 patients undergoing hemodialysis who received patiromer for hyperkalemia found that treatment with patiromer was associated with a mean reduction in serum K þ of 0.5 mEq/L. 106 In this study, the proportion of patients with severe hyperkalemia (serum K þ !6.0 mEq/L) decreased from 64% at baseline to 23% after initiation of patiromer. 106 However, long-term real-world experience is needed to confirm the safety of patiromer and SZC if used as maintenance therapy.…”
Section: Real-world Experience With K þ Bindersmentioning
confidence: 79%
“…106 In this study, the proportion of patients with severe hyperkalemia (serum K þ !6.0 mEq/L) decreased from 64% at baseline to 23% after initiation of patiromer. 106 However, long-term real-world experience is needed to confirm the safety of patiromer and SZC if used as maintenance therapy. 76,89 CONCLUSION Sodium zirconium cyclosilicate and patiromer have been found to be effective and tolerable in clinical trials and are viable alternatives to SPS for the management of hyperkalemia in patients with CKD.…”
Section: Real-world Experience With K þ Bindersmentioning
confidence: 96%
“…1 Patients undergoing maintenance HD have a high risk of hyperkalemia, generally defined as serum potassium (K þ ) concentrations of >5.0 mmol/l, even when receiving adequate treatment with 3-times-weekly HD (Figure 1). 2,3 Hyperkalemia is a potentially lifethreatening disorder that can cause arrhythmias and sudden cardiac arrest. 3,4 In a US cohort study of patients undergoing HD between 2007 and 2010, the rate of hyperkalemia (K þ $5.5 mmol/l) was 16.3 to 16.8 per 100 patient-months.…”
mentioning
confidence: 99%